ANALISIS BIAYA DAN PENDAPATAN USAHATANI PADI DI KABUPATEN KARANGANYAR - Umi Barokah; Wiwit Rahayu; Mei Tri Sundari (Agric, 2014)
Rice is the food crop with the harvested area and production of the highest among other food crops in Karanganyar Regency. From year to year, its harvested area, production, and productivity tend to increase. These increments showed that rice farming is still in demand by farmers. This study aims to analyze the cost, revenue, and efficiency of rice farming in this regency. The study was conducted in 4 districts; Gondangrejo, Karanganyar, Jaten, and Jatipura. From each district were taken two villages. In total, there were 159 farm households sampled randomly. In average,the revenue of rice farming in Karanganyar is Rp14,429,117.37/ha/year with yearly costs of Rp7,142,446.39/ha. The average annual income therefore reaches Rp7,286,670.98/ha. The value of rice farming efficiency is 2.02 indicating that rice farming in Karanganyar is worth the effort.